Characterization of Al2O3 Thin Films Prepared by Thermal ALD. (August 2015) - Barbos, Corina; Blanc-Pelissier, Danièle; Fave, Alain; Blanquet, Elisabeth; Crisci, Alexandre; Fourmond, Erwann; Albertini, David; Sabac, Andreï; Ayadi, Khaled; Girard, Philippe; Lemiti, Mustapha
Abstract: Thermal Atomic Layer Deposition was used to deposit Al2 O3 layers with thickness ranging from 2 to 100 nm for surface passivation of silicon solar cells. Various characterization techniques were used to evaluate the chemical, physical and optical properties of the layers and interfaces. Minority carrier lifetime around 2 ms was measured for an optimal thickness of 15 nm for as-deposited layers on high resistivity n-type silicon substrate. An annealing step at 400 °Cincreases lifetime up to 5.7ms for the same structure.